2020
DOI: 10.1155/2020/4939310
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I Prevents Cellular Aging via Activation of Mitophagy

Abstract: Mitochondrial dysfunction is a hallmark of cellular aging. Mitophagy is a critical mitochondrial quality control mechanism that removes dysfunctional mitochondria and contributes to cell survival. Insulin-like growth factor 1 (IGF-1) promotes survival of smooth muscle cells (SMCs), but its potential effect on cellular aging is unknown yet. We found that IGF-1 decreased cell senescence, prevented DNA telomere shortening, increased mitochondrial membrane potential, activated cytochrome C oxidase, and reduced mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…In particular, IGF-1 mediates a protective mitochondrial signal that is transduced into the cell through the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2). By coupling mitochondrial biogenesis with the induction of BNIP3 (a member of the apoptotic Bcl-2 protein family), this pathway increases autophagosome turnover and improves cell survival, even in the presence of metabolic or mitochondrial stress [84]. In recent years, IGF-1 signaling has been shown to modify mitochondrial function and capacity (including mitochondrial DNA/RNA ratio management), organelle biogenesis, oxidative phosphorylation and suppression of ROS production [85].…”
Section: Igf-1mentioning
confidence: 99%
“…In particular, IGF-1 mediates a protective mitochondrial signal that is transduced into the cell through the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2). By coupling mitochondrial biogenesis with the induction of BNIP3 (a member of the apoptotic Bcl-2 protein family), this pathway increases autophagosome turnover and improves cell survival, even in the presence of metabolic or mitochondrial stress [84]. In recent years, IGF-1 signaling has been shown to modify mitochondrial function and capacity (including mitochondrial DNA/RNA ratio management), organelle biogenesis, oxidative phosphorylation and suppression of ROS production [85].…”
Section: Igf-1mentioning
confidence: 99%
“…PINK1 is a prime mitophagy regulator.The silencing of PINK1 suppressed mitophagy and inhibited IGF-1-induced anti-ageing impacts in aged SMC, as expected with the pertinent function of mitophagy on the impact ofIGF-1 in cellular ageing. IGF-1 inhibited cellular ageing viaNrf2/ Sirt3-dependent mitophagy activation[20]. Thus, the findings suggest that IGF-1 signaling activation is a viable potential approach for mitophagy activation and retardation of cellular ageing.…”
mentioning
confidence: 80%
“…An antiageing effect was suggested on detection that IGF-1 diminished cell senescence, inhibited DNA telomere shortening, augmented mitochondrial membrane potential, activated cytochrome C oxidase, and minimized mitochondrial DNA derangement in sustained cultured (aged) aortic SMC. IGF-1 enhanced mitophagy in aged cells, and it was associated with mitigated expression of cyclin-dependent kinase inhibitors p16 and p21 and augmented levels of Nrf2 and Sirt3[20], biogenesis in regulators of mitophagy and mitochondria. SiRNAinduced suppression of either Nrf2 or Sirt3 obliterated IGF-1-induced upregulation of mitophagy.…”
mentioning
confidence: 95%
“…The maintenance of smooth muscle cells is potentiated by insulin-like growth factor 1, IGF-1. However, its potential impact on cellular aging [50] or senescence remains unelucidated. IGF-1 was found to diminish cell aging, disrupt DNA telomere dissipation, elevate mitochondrial membrane capacity and capability and cytochrome coxidase activation as well as mitigation of mitochondrial DNA injury in aged or derelict cultured aortic smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the Nrf2/Sirt3 pathway was pertinent for the impact of IGF-1 on mitophagy. A perspicuous regulator of mitophagy is PINK1 that obliterates suppressed mitophagy and inhibited IGF-1-induced anti-aging influences in decrepit smooth muscle cells as characteristic of mitophagy in the impact of IGF-1 in cellular senescence [50]. It is perspicuous that IGF-1 constrains cellular senescence or aging through Nrf2/Sirt3-dependent mitophagy activation.…”
Section: Discussionmentioning
confidence: 99%